Invasive Malassezia pachydermatis Infection in an 8-Year-Old Child on Lipid Parenteral Nutrition - Zheyi Teoh; Joel Mortensen; Joshua K. Schaffzin (Case Reports in Infectious Diseases)
Invasive disease due to Malassezia pachydermatis infection is uncommon but increasingly recognized in children, especially neonates on parenteral nutrition or immunocompromised children. We describe a case of Malassezia pachydermatis fungemia in a demographically distinct patient and discuss the workup and current strategies for managing this infection in the setting of a central venous catheter.